Unilateral Versus Bilateral Frontalis Suspension Sling Surgery for Correction of Severe Unilateral Congenital Ptosis. - Jyoti Dhaka; Ashok Kumar Grover (Asian Journal of Medical Research, 2020)
Background: To compare the surgical outcome of unilateral silicone sling with bilateral fascia latafrontalis suspension surgery for severe unilateral congenital ptosis.Subjects and Methods:This prospective, interventional and comparative study examined 30 patients of severe unilateral congenital ptosis. 30 patients were divided in to 2 groups, group 1 included 15 patients who underwent unilateral silicone sling frontalis suspension surgery and group 2 included 15 patients who underwent contralateral levator excision with bilateral fascia latafrontalis sling surgery.Results:Mean improvement in MRD1 after surgery in group 1 who underwent unilateral silicone sling surgery was 3.9+1.18 mm and in group 2 who underwent bilateral fascia lata it was 4.9+0.89 mm (p value 0.0001). Excellent results (difference of lid height <1 mm) were seen in 93.3% patients who underwent bilateral fascia latafrontalis sling while in 73.3% patients of unilateral silicone sling. All patients who underwent bilateral fascia lata showed excellent lid crease (symmetric without obliteration) and 80% of the patients who underwent unilateral silicone sling surgery (p value 0.032).Conclusion: Functional and cosmetic outcomes regarding MRD1, symmetry of lid height, lid crease were noted better in group 2 patients who underwent contralateral levator excision with bilateral fascia latafrontalis suspension surgery as compared to group 1 patients who underwent unilateral silicone sling surgery.